Imaging near-field compton backscattered X-rays using Pinhole and coded masks - Munoz, Andre Arelius Marcus (Cranfield University, 2019)
Research was conducted to understand the behaviour of an X-ray backscatter imaging system using coded masks to view complex scenes. These spatially multiplexing images were compared to those collected using a single pinhole and a commercial flying spot (time multiplexing) imaging system. An X-ray backscatter system was constructed to perform experiments with pinholes and coded masks. A novel fabrication technique adopting 3D printing was developed to rapidly create low-cost alternatives to the traditional drilled tungsten coded masks. Subsequently, this allowed for the retention of ideal square open elements within the mask, along with the benefit of having a self-supporting structure. Conventional methods of manufacturing coded masks compromise the encoding process by using round holes in place of the square elements to achieve a self-supporting structure. Previous work has suggested that coded masks with a low open fraction (i.e. < 0.5) will yield a higher signal-to-noise ratio than those with a 0.5 open fraction. As part of this study, the following low open fraction coded mask was calculated; dilute uniformly redundant array (DURA), Singer and the biquadratic residue (BR). In total 111 new array patterns were calculated. Xray backscatter images are presented from examples of these coded masks with images reconstructed via cross-correlation and blind deconvolution. Overall, for coded mask imaging, the best results were from the 19 MURA for its signalto-noise with a typical 2-12 second (s) exposure time. Consequently, there was little evidence to support the benefit of lower open fractions. Pinhole and coded mask images were somewhat comparable with the pinhole requiring a longer exposure time of 60-300 s. While not ideal due to barrel distortion, the images from the flying spot system exhibited higher signal-to-noise ratios and resolutions but required an exposure time of 70 seconds, longer than those for the MURA